2013
DOI: 10.3390/ijms140610944
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Altered Wnt1/β-Catenin Expression on Clinicopathology and Prognosis in Clear Cell Renal Cell Carcinoma

Abstract: In renal cell carcinoma (RCC), single members of the Wnt/β-catenin signaling cascade were recently identified to contribute to cancer progression. However, the role of Wnt1, one of the key ligands in β-catenin regulation, is currently unknown in RCC. Therefore, alterations of the Wnt1/β-catenin axis in clear cell RCC (ccRCC) were examined with regard to clinicopathology, overall survival (OS) and cancer specific survival (CSS). Corresponding ccRCCs and benign renal tissue were analyzed in 278 patients for Wnt1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 37 publications
2
66
0
Order By: Relevance
“…The Wnt/β-catenin pathway is frequently disrupted in RCC by promoter methylation of key pathway regulators (FIG. 3a), and unregulated β-catenin activation increases the tumourgenicity of renal cells 74 . In addition, VHL is inactivated in ~11-30% of ccRCC and pRCC by promoter methylation [75][76][77] or by loss of chromosome 3.…”
Section: Frequently Dysregulated Pathways Wnt-β-catenin Met and Slitmentioning
confidence: 99%
“…The Wnt/β-catenin pathway is frequently disrupted in RCC by promoter methylation of key pathway regulators (FIG. 3a), and unregulated β-catenin activation increases the tumourgenicity of renal cells 74 . In addition, VHL is inactivated in ~11-30% of ccRCC and pRCC by promoter methylation [75][76][77] or by loss of chromosome 3.…”
Section: Frequently Dysregulated Pathways Wnt-β-catenin Met and Slitmentioning
confidence: 99%
“…Several studies indicate that high β-Catenin- expression is associated with worse clinical and pathological features. It could be shown that high β-Cateninexpression is associated with higher grading [15] and advanced stage, vascular invasion, and tumor necrosis [21]. However, other studies could not prove the correlation with adverse clinical and pathological parameters [18,26,28].…”
Section: Discussionmentioning
confidence: 89%
“…Krabbe et al [18] could identify an association between reduced β-Catenin-expression and worse RFS and CSS, whereas there are several studies showing no association between β-Catenin-expression and survival [26,28]. Furthermore, there are several studies suggesting a worse prognostic effect of high cytoplasmic β-Catenin expression and worse survival [15,21,22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A compelling clinical study validated that the Wnt ligand receptors Frizzled 5 (FZD5) and FZD8 were markedly increased in renal carcinoma samples [13]. Enhanced RCC aggressiveness was reflected in altered Wnt1/β-catenin canonical signaling, and β-catenin was determined to be related to unfavorable clinicopathology and impaired survival [14]. Moreover, the Wnt/β-catenin pathway was identified as exerting functions in inducing P-gp overexpression in chronic myeloid leukemia [15].…”
Section: Introductionmentioning
confidence: 97%